Identification and validation of hub genes and pathways associated with mitochondrial dysfunction in hypertrophy of ligamentum flavum - Gu, Yifei; Yu, Wenchao; Qi, Min; Hu, Jinquan; Jin, Qianmei; Wang, Xinwei; Wang, Chen; Chen, Yu; Yuan, Wen (Frontiers in Genetics, 2023)
Background: Lumbar spinal stenosis which can lead to irreversible neurologic damage and functional disability, is characterized by hypertrophy of ligamentum flavum (HLF). Recent studies have indicated that mitochondrial dysfunction may contribute to the development of HLF. However, the underlying mechanism is still unclear. Methods: The dataset GSE113212 was obtained from the Gene Expression Omnibus database, and the differentially expressed genes were identified. The intersection of DEGs and mitochondrial dysfunction-related genes were identified as mitochondrial dysfunction-related DEGs. Gene Ontology analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and Gene Set Enrichment Analysis were performed. Protein-protein interaction network was constructed, and miRNAs and transcriptional factors of the hub genes were predicted via the miRNet database. Small molecule drugs targeted to these hub genes were predicted via PubChem. Immune infiltration analysis was performed to evaluate the infiltration level of immune cells and their correlation with the hub genes. In final, we measured the mitochondrial function and oxidative stress in vitro and verified the expression of hub genes by qPCR experiments. Results: In total, 43 genes were identified as MDRDEGs. These genes were mainly involved in cellular oxidation, catabolic processes, and the integrity of mitochondrial structure and function. The top hub genes were screened, including LONP1, TK2, SCO2, DBT, TFAM, MFN2. The most significant enriched pathways include cytokine-cytokine receptor interaction, focal adhesion, etc. Besides, SP1, PPARGC1A, YY1, MYC, PPARG, and STAT1 were predicted transcriptional factors of these hub genes. Additionally, increased immune infiltration was demonstrated in HLF, with a close correlation between hub genes and immune cells found. The mitochondrial dysfunction and the expression of hub genes were validated by evaluation of mitochondrial DNA, oxidative stress markers and quantitative real-time PCR. Conclusion: This study applied the integrative bioinformatics analysis and revealed the mitochondrial dysfunction-related key genes, regulatory pathways, TFs, miRNAs, and small molecules underlying the development of HLF, which improved the understanding of molecular mechanisms and the development of novel therapeutic targets for HLF.